2006
DOI: 10.1002/nbm.1059
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion, diffusion and spectroscopy values in newly diagnosed cerebral gliomas

Abstract: Purpose To evaluate perfusion, diffusion, and spectroscopy values in enhancing and non-enhancing lesions for patients with newly diagnosed gliomas of different grades. Materials and Methods Sixty-seven patients with newly diagnosed glioma were entered into the study 20 grade II, 26 grade III and 21 grade IV. MR data were acquired at 1.5T and included diffusion weighted images (59/67 patients), dynamic perfusion weighted images (30/67 patients) and 3D H-1 MR spectroscopy (64/67 patients). Enhancing and non-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 37 publications
(41 reference statements)
7
69
1
6
Order By: Relevance
“…In a recent paper, Chang et al (187) have shown that while this may be the case for area of macroscopic tumor within the enhancing volume of grade IV glioma, it is not consistent with the values in grade II and grade III glioma. Catalaa et al (204) observed a negative correlation between mean ADC and mean Cho for patients with newly diagnosed grade IV gliomas, but not for grade II or grade III gliomas. Khayal et al (205) were unable to detect a correlation between Cho levels in the contrast enhancement or necrotic core and ADC in grade IV gliomas, but they found a negative correlation between median Cho and ADC in the non-enhancing lesion and the overall T2-hyperintensity.…”
Section: Correlation Analysismentioning
confidence: 97%
“…In a recent paper, Chang et al (187) have shown that while this may be the case for area of macroscopic tumor within the enhancing volume of grade IV glioma, it is not consistent with the values in grade II and grade III glioma. Catalaa et al (204) observed a negative correlation between mean ADC and mean Cho for patients with newly diagnosed grade IV gliomas, but not for grade II or grade III gliomas. Khayal et al (205) were unable to detect a correlation between Cho levels in the contrast enhancement or necrotic core and ADC in grade IV gliomas, but they found a negative correlation between median Cho and ADC in the non-enhancing lesion and the overall T2-hyperintensity.…”
Section: Correlation Analysismentioning
confidence: 97%
“…However, often a high-grade glioma may be mistaken for a low-grade glioma when it demonstrates minimal edema, no contrast material enhancement, no necrosis, and no mass effect. Moreover, large cerebral gliomas are often histopathologically heterogeneous and may have components of varying grades of malignancy within them [1] . Therefore, accurate preoperative grading of gliomas and planning of adequate treatment strategies are often difficult with conventional MR imaging alone.…”
Section: Hmrs In the Preoperative Grading And Outcome Prediction Of mentioning
confidence: 99%
“…This finding agreed with previously published data showing no significant correlation between volumes of elevated lactate and any morphologic abnormality. 20 Our results suggest that a reduction in creatine levels and the presence of regions with abnormal vasculature may be considered as noninvasive markers of tumor progression from grade III to grade IV gliomas. Increased cellular proliferation, as indicated by elevated choline in the aPH region of grade III gliomas, may initially cause dilation of existing blood vessels and/or the formation of new ones.…”
Section: Discussionmentioning
confidence: 68%
“…Contralateral normal tissue was also included as a reference for postprocessing of metabolites and region definition. 20 K-space sampling was restricted to the central ellipsoidal region within a 12 ϫ 12 ϫ 8 phase-encode matrix to shorten the acquisition time to approximately half that of the full k-space sampling. 33 This technique allowed separation of lactate from lipid within the same total acquisition time (ϳ17 minutes).…”
Section: Mr Imaging and Spectroscopic Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation